Effects of goat social rank on kid gender - C. Tölü; T. Savaş; A. Pala; H. Thomsen (Czech Journal of Animal Science, 2007)
Mechanisms of gender ratio in progeny are complex and the fine details are still largely unknown, even in mammals. Though the 50% ratio of males and females is expected, various factors have been shown to be effective in diverting the ratio from the expected. In this study, dominance index, effects of sire, age of dam, birth type and year of birth on the gender ratio of Turkish Saanen goat kids were investigated in a full model. The analysis indicated that dominance index (DI) of the dam had a significant influence on the gender ratio of kids (P = 0.036). Certain sires tended to father female descendants repeatedly and the dams with high dominance index gave birth to male kids. Effects of sire on kid gender approached significance (P = 0.094). Age of dam, year and birth type were insignificant.